UPAYA MENDORONG PARTISIPASI REMAJA AL-BAHAR DALAM PEMELIHARAAN KEBERSIHAN LINGKUNGAN SEKITAR SUMBER AIR - Elis Anisah Fitriah (Psympathic : Jurnal Ilmiah Psikologi, 2012)
This intervention program aims to increase trust of the members of Al Bahar community towards the well water. This is done by increasing active participation of the adolescents Al Bahar in looking after the environmental hygiene surrounding the wells. Community participation and empowerment techniques were applied to encourage adolescents to perform as change agents in the community. This program has been executed for approximately 2 (two) months with the active involvement of 15 (fifteen) adolescents. Experiential learning and participatory approaches such as games, role plays, and discussions, and other fun activities were used to stimulate adolescence’s participation.        The program evaluation of this intervention has showed some significant indications for changes among the adolescents. The changes are among others: the establishment of an informal organization of adolescence to maintain their activities; awareness and willingness to take care of the environmental hygiene in the area; coming up with ideas to solve some contextual environmental problems. By listening and respect the voices of this adolescence they become more confident. By letting them to participate actively in the programs they felt a sense of belonging towards the program achievement and the environment as well.